A Comparative Study of Intravenous Nitroglycerin With or Without Intravenous Lignocaine for Attenuation of Stress Responses to Endotracheal Intubation - Regmi, Nabin Kumar; Singh, Grisuna (Journal of Nepalgunj Medical College, 2018)
Background: Laryngoscopy and tracheal intubation lead to stress response which is characterized by transient rise in blood pressure and heart rate. This response is tolerated well in normal individuals but can lead to significant morbidity and mortality in patients with cardiovascular and cerebrovascular diseases. Search for the better drugs to suppress these responses is going on through decades. Aim of Study: To compare the effects of IV nitroglycerin alone and in combination with IV lignocaine, on attenuation of stress response to end tracheal intubation. Material and Methods: This is a randomized, double blind study conducted in 60patients admitted for operation at NGMCTH, between June 2018 to November 2018. Patients were of 16- 60 years age groups and belonging to ASA group I and II. Patients were divided into two groups: Group I IV Nitroglycerin 500 mcg+ NS 3 ml. (n=30) and Group IIIV Nitroglycerin 500 mcg+ IV Lignocaine 63 mg (n=30). Systolic Blood Pressure (SBP), Diastolic Blood Pressure (DBP), Mean Arterial Pressure (MAP) and Heart rate (HR) were measured and Rate Pressure Product (RPP) calculated.Results: Baseline values were comparable in both groups. Post Intubation, there was significant decrease in SBP at 0,1,3 and 5 minutes while DBP and MAP significantly decreased at 1, 3 and 5 minutes, in both groups. Significant tachycardia was noted in both groups at 0,1and 3 minutes, and RPP remained unchanged in both groups.Conclusion: Nitroglycerin significantly decreases blood pressure, prevents rise in RPP but does not attenuate heart rate after end tracheal intubation. There is no benefit of adding IV lignocaine to IV nitroglycerin for attenuation of stress response to end tracheal intubation.